Psychological Well-Being Mediates Cyberbullying Victimization and Risky Health Behavior: Public Health Implications for Universities - Nugroho, Purwo Setiyo; Bhubate Samutachak; Tawanchai Jirapramukpitak; Fatimah Ahmad Fauzi; Ghozali, Ghozali; Aphichat Chamratrithirong (Journal of Public Health and Pharmacy, 2025)
Introduction: Cyberbullying has become a burden in the current digital world and has an impact on health status, including physical and mental health. People try to mitigate these mental health issues through various coping strategies, including engaging in risky health behavior. Such risky health behaviors may have implications for future health status. Thus, this study aims to examine the prevalence of cyberbullying victimization and elucidate the consequences of cyberbullying victimization on psychological well-being and risky health behavior. Methods: A cross-sectional design was employed in this study, with 700 undergraduate students as research participants. The students were randomly selected using proportional stratified and random sampling in a selected university in Samarinda, Indonesia, between January and March 2024. Participants were first-year, second-year, third-year, and fourth-year students. Self-administered data collection using a standard questionnaire for each variable. This study used the Structural Equation Model to analysed the associations between variables. Results: Cyberbullying victimization affects psychological well-being, which, in turn, influences risky health behaviors. While no direct link was found between cyberbullying and risky health behaviors, psychological well-being fully mediates this relationship. This suggests that the negative impact of cyberbullying on health behaviors occurs through its detrimental effects on psychological well-being, leading to risky health behaviors as coping strategies. Conclusion: The study reveals significant links between cyberbullying victimization, coping capacity, psychological well-being, and risky health behavior. These findings highlight the importance of effective coping strategies. Future research should focus on enhancing problem-focused coping techniques, which could serve as positive strategies to reduce the negative impact of cyberbullying on psychological health and risky health behaviors.